Correlation of Indonesia's Intangible Cultural Heritage and American Popular Culture in the Animated Film Raya and the Last Dragon (2021) - Wantasen*, Isnawati Lydia; Sigarlaki, Stephani Johana; Claudia, Tatiana Starry (Universitas Syiah Kuala, 2023)
Culture in the dictionary of the Indonesian language can be understood as mind, reason and custom. Culture or culture that is preserved in descent is what is called a cultural heritage. Intangible cultural heritage is intangible, like concepts and technologies. And its nature can pass and disappear over time as the times evolve such as language, music, dance, ceremonies, and various other structured behaviors. American popular culture is all forms of thought, action, or belief that imply a mass product. The animated film Raya and the Last Dragon is an American popular cultural product that contains the cultural heritage of Indonesia, including batik, keris, and silat. American popular culture is perpetuating the indigenous cultural heritage of Indonesia through the screening of this animated film. The preservation of local culture is respected through the dissemination of films by taking elements of plot, background, figure and consolidation. The theory used is from Wellek and Warren that deals with the intrinsic elements of a literary work, and is supported by the American popular culture theory of Derry Mayendra.